2003
DOI: 10.1016/s0195-668x(03)00442-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic statins interfere with the inhibitory effects of clopidogrel on platelet function — a flow cytometry study

Abstract: Certain statins which are substrates of the CYP3A4 isoform competitively inhibit the metabolic activation of clopidogrel. As a result the relative clopidogrel induced platelet inhibition (P-selectin-expression) is diminished--but still there is a relative clopidogrel effect of more than 80% in the maintenance phase. It may be reasonable to test the therapeutic efficacy of clopidogrel in those patients who require long-term treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
2
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 20 publications
6
116
2
8
Order By: Relevance
“…3 They found no significant difference in mortality and stroke incidence among patients receiving atorvastatin compared with other statins. However, this study was limited as a nonrandomized, retrospective, observational study, and the comparison of atorvastatin to "other statins" was irrespective of CYP3A4-metabolism.…”
Section: Responsementioning
confidence: 96%
See 2 more Smart Citations
“…3 They found no significant difference in mortality and stroke incidence among patients receiving atorvastatin compared with other statins. However, this study was limited as a nonrandomized, retrospective, observational study, and the comparison of atorvastatin to "other statins" was irrespective of CYP3A4-metabolism.…”
Section: Responsementioning
confidence: 96%
“…This post hoc evaluation unfortunately was not adequately powered to assess event rates in the pravastatin group. Given these data and the in vivo data published by Lau et al 2 and more recently by Neubauer et al, 3 the potential for a significant interaction between clopidogrel and statins that are CYP3A4 substrates cannot be discounted. Because of limitations with post hoc and observational study evaluations of drug interactions, well-designed clinical trials are needed to specifically evaluate this interaction.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In subgroup analysis of patients using atorvastatin, which is lipophilic and is reportedly competes with clopidogrel for the cytochrome P450 system, 19,20 groups B and C showed superior P2Y 12 inhibition to group A. The difference in P2Y 12 inhibition between groups B and C did not exceed the predetermined limit of noninferiority ( Figure 6).…”
Section: Adverse Eventmentioning
confidence: 97%
“…Some investigators have reported that differences in lipophilicity of statins may influence the antiplatelet action of clopidogrel. 19,20 We therefore decided to control the statin used to avoid potential controversy in interpretation of data.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%